Earthquake Resistance of Masonry-Infilled RC Frames Strengthened with Expanded Metal - Kusonkhum, Wuttipong; Tankasem, Phongphan; Leeanansaksiri, Anuchat (Civil Engineering Journal, 2024)
This research aimed to investigate the compressive strength of lightweight concrete walls before and after reinforcement using the expanded metal reinforced with ferrocement jacketing method and to evaluate the performance level of lightweight concrete walls in reinforced concrete rigid frames. Masonry infill walls were tested using seven samples of lightweight concrete with an average size of 600×600 mm under axial force. The study results were found that in the part of control, non-plastered lightweight concrete wall (CWL) bore an average compressive strength of 2.52 MPa, and plastered lightweight concrete (WPL) bore an average compressive strength of 2.95 MPa. It indicated that plastering on masonry infill walls was able to bear higher impact strength at 1.17 times due to the bonding force of plastering cement at the masonry infill wall. Lightweight concrete walls reinforced with expanded metal, which were able to bear the maximum compressive strength, were lightweight concrete walls reinforced with 1 layer of expanded metal (WPL-E1) that bore the maximum compressive strength capacity, which was equal to 6.40 MPa. When compared with plastered lightweight concrete walls (WPL) samples, masonry infill walls had 2.16 times higher strength capacity. It was shown that reinforcement using the ferrocement technique significantly increased compressive strength capacity. However, in this research, WPL samples, the plastered lightweight concrete walls, were selected as the control samples, and WPL-E1 test samples with the highest compressive strength were used to evaluate the performance level of the reinforced concrete rigid frame. It was found that lightweight concrete walls reinforced with expanded metal were able to bear higher strength at 1.92 and 3.66 times, respectively. When compared to unreinforced masonry infill wall samples and the bare rigid frame, reinforcement with expanded metal effectively was able to increase the strength and stiffness of the reinforced concrete rigid frame. Doi: 10.28991/CEJ-2024-010-12-017 Full Text: PDF